Retroperitoneoscopic Varicocelectomy in Adolescents: Long-term Follow-up in Two Italian Centres - Molinaro Francesco; Cobellis Giovanni; Cerchia Elisa; Ferrara Francesco; Tallarico Rosella; Sica Marina; Noviello Carmine; Martino Ascanio; Angotti Rossella; Messina Mario (Wolters Kluwer Medknow Publications, 2017)
Background: The varicocele is the most commonly diagnosed pre-pubertal andrological condition with an incidence of 10%-15% between adolescents. The aim of this study was to evaluate the efficacy of retroperitoneoscopic varicocelectomy (RV) in two Italian centres with particular attention to post-operative testicular volume and semen analysis after 18 years of life. Materials and Methods: From 1999 to 2010, 286 adolescents underwent retroperitoneoscopic left varicocelectomy. Of these patients, 67 were evaluated by clinical examination, ultrasound and semen analysis, allowing an adequate long-term follow-up. Results: Surgery was performed at a mean age of 13 years (range 10-17) without intraoperative complications. There were two recurrences (3%), two left testis hypotrophy (3%) and four hydroceles (6%), not yet undergone surgery because asymptomatic or without tension. Currently, 44 patients accepted to perform semen analysis which showed a reduction in sperm motility in 12 cases, with associated morphological alterations in 3 and reducing number of spermatozoa in one case. Conclusions: In consideration of morphological and biomolecular spermatic alterations reported in adolescent varicocele that could interfere with cellular migration, differentiation and nutrition, it is fundamental to consider the correction of varicocele, not only for the classical indications, but also as a choice for arresting the progressive damage that inevitably acts for several years on the adolescent testis. The RV in adolescents is a safe and feasible procedure for experienced paediatric laparoscopic surgeons with early good clinical outcomes, but more studies occur to understand the real impact of adolescent varicocelectomy on testicular function.